TRANSFORMASI MANAJEMEN MASYARAKAT DI LINGKUNGAN PESANTREN - Yayan Herdiana; Cucu Abdul Kosim; Mohamad Erihadiana; Muhibbin Syah (Universitas Pakuan, 2021)
TRANSFORMATION OF COMMUNITY MANAGEMENT IN THE PESANTREN ENVIRONMENTIslamic boarding schools are the oldest educational institutions in Indonesia. He was born from the concept of a mandala to spread religion in the archipelago, they Islamized the hermitage into a pesantren. The development of the pesantren is quite tough, because the pesantren is strong in maintaining tradition while the community wants progress. The demands of the global and millennial community require pesantren to transform their management processes, especially the methods of managing communities within the pesantren. This paper wants to know how Islamic boarding schools respond to community demands? The method of this research is field reaserch research (field study) using a descriptive qualitative approach. To obtain data, researchers conducted field observations, documentation studies, and in-depth interviews. The results showed that in carrying out the transformation of community management in the pesantren environment, the Raudhatutta'allum pesantren did the following: (1) change the leadership pattern from a single or mono pattern to a collegial collective; (2) in implementing the change pattern of community management in the pesantren environment, the Raudhatutta'allum pesantren still maintains old values which are still considered good, including KH Engking Syarifudin (late) charisma immortalized as the foundation's name; (3) adaptive, responsive and accommodating to the demands and desires of the surrounding community; (4) empowerment of human resources by sharing responsibilities through clear job descriptions among the heirs or the families of elderly kyai; (5) santri service program to eliminate the gap between pesantren and the surrounding community; (6) binding pesantren alumni through the Raudhatutta'allum alumni association forum. The method of transforming community management in the pesantren environment was effective and the indication was the development of the quality and access of the Raudhatutta'allum pesantren.